Building an Islamic Learning Rhythm by Strengthening Spiritual Teaching Based on Canva's Interactive Media - Nadila Maryam; Saca Suhendi; Miftahul Fikri (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study aimed to examine the effect of the Spiritual Teaching approach assisted by Canva interactive digital media on students' learning motivation in Islamic Religious Education (IRE). The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The participants consisted of 54 eighth-grade students of SMP Labschool Percontohan UPI Cibiru, Bandung, Indonesia, who were divided into an experimental class and a control class. Data were collected through learning motivation questionnaires, observations, interviews, and documentation and were analyzed using descriptive and inferential statistics, including normality, homogeneity, independent samples t-test, and N-Gain analyses with the assistance of SPSS version 31. The findings revealed that students in the experimental class experienced a higher increase in learning motivation than those in the control class. The independent samples t-test showed a significance value of less than 0.05, indicating a significant effect of the implementation of the Spiritual Teaching approach assisted by Canva interactive digital media on students' learning motivation. These findings suggest that integrating spiritual values with interactive digital technology can provide a meaningful and engaging learning experience and may serve as an innovative pedagogical alternative for addressing the crisis of students' learning motivation in the digital era.